A STUDY ON FAMILY PLANNING PRACTICES AND METHODS AMONG WOMEN OF URBAN SLUMS OF LUCKNOW CITY - Kumar, Arjit; Bhardwaj, P; Srivastava, J P; Gupta, P (Indian Journal of Community Health, 2011)
Background: Utilization of family planning methods, their side effects and the factors influencing their uses. Aims: To study the family planning practices/methods among the married women of reproductive age (15- 45yrs). Study Design: Community-based study. Study Subjects: The Women of reproductive age groups (15-45yrs) adopting family planning methods & those residing in urban slums of, Lucknow. Sample size: 540, Study Period : July 2009 to July 2011. Sampling Technique: thirty cluster sampling. Result: The acceptance of family planning methods both temporary and permanent methods increased with level of literacy of women. About 53.40 % adopted I.U.C.D, 38.83% O.C pills & only 7.77% of their partners used condoms. 66.6% have undergone laparoscopic & 33.4% mini-lap sterilization. Vasectomy was not done for even a single partner. More number of illiterate and primary educated accepted permanent method after 3 or more children than higher educated who accepted it after 1 or 2 children. Among acceptors of permanent methods, total 70.27 % were experiencing side effects and among temporary method users, it accounted 23.30%. Conclusions: Acceptance in family planning is associated with increasing age, nuclear family & level of literacy. IUCD is the most accepted one among all the temporary methods. Vasectomy and newer contraceptives were not at all used.